LEE CRONIN'S THE MUMMY - Reynor, Jack; Costa, Laia; Grace, Natalie; Calamawy, May (New Line Cinema / Warner Home video, 2026)
In Lee Cronin's The Mummy, the young daughter of a journalist disappears without a trace in the desert. Eight years later, the shattered family is stunned when the girl suddenly reappears. But what should have been a joyful reunion quickly spirals into a true nightmare.